Targeting Gpr52 lowers mutant HTT levels and rescues Huntington's disease-associated phenotypes - Song, Haikun; Li, Hexuan; Guo, Shimeng; Pan, Yuyin; Fu, Yuhua; Zhou, Zijian; Li, Zhaoyang; Wen, Xue; Sun, Xiaoli; He, Bingqing; Gu, Haifeng; Zhao, Quan; et al. (Brain (London, England : 1878), 2018)
See Huang and Gitler (doi:10.1093/brain/awy112) for a scientific commentary on this article. Small molecule drugs that can reduce levels of the mutant huntingtin protein (mHTT) are sought for the treatment of Huntington's disease. Song et al. demonstrate that deleting Gpr52, or inhibiting Gpr52 protein function with a novel small molecule antagonist, reduces mHTT levels and rescues Huntington's disease-associated phenotypes in cellular and mouse models. Abstract See Huang and Gitler (doi:10.1093/brain/awy112) for a scientific commentary on this article. Lowering the levels of disease-causing proteins is an attractive treatment strategy for neurodegenerative disorders, among which Huntington's disease is an appealing disease for testing this strategy because of its monogenetic nature. Huntington's disease is mainly caused by cytotoxicity of the mutant HTT protein with an expanded polyglutamine repeat tract. Lowering the soluble mutant HTT may reduce its downstream toxicity and provide potential treatment for Huntington's disease. This is hard to achieve by small-molecule compound drugs because of a lack of effective targets. Here we demonstrate Gpr52, an orphan G protein-coupled receptor, as a potential Huntington's disease drug target. Knocking-out Gpr52 significantly reduces mutant HTT levels in the striatum and rescues Huntington's disease-associated behavioural phenotypes in a knock-in Huntington's disease mouse model expressing endogenous mutant Htt. Importantly, a novel Gpr52 antagonist E7 reduces mutant HTT levels and rescues Huntington's disease-associated phenotypes in cellular and mouse models. Our study provides an entry point for Huntington's disease drug discovery by targeting Gpr52.